Group Nominations as an Instrument of Electoral Struggle: Ukrainian Discourse of 2019 Parliamentary Elections - Boyko, Dmytro; Zaporozhchenko, Ruslan; Lytovchenko, Artem; Nekhaienko, Oksana; Yashkina, Daria (Волинський національний університет імені Лесі Українки, 2021)
The authors work within the framework of political sociology using interdisciplinary methodology. The article presents the results of a sociological analysis of the functions of group nominations in the electoral struggle in divided societies. The empirical basis of the article is the author's study of the electoral discourse based on the material of the parliamentary elections in Ukraine in 2019, carried out within the framework of the ARDU international research project, as well as a mass poll conducted within the framework of the same project. The authors investigate the electoral struggle as a factor and s reflection of macrosocial processes, relying on a combined theoretical and methodological foundation: the sociology of cleavages, social constructivism, and critical discourse analysis. The results of the analysis of the pre-election discourse and a mass survey of the adult population of Ukraine show the relationship between discursive group nominations and objective social cleavages. The division of society into conflict groups is used as a discursive tool for segmentation of the electoral audience, as well as for the consolidation and deepening of existing social divisions. Authors conclude that there is the interrelation between discursive group nominations and objective social cleavages. Group nominations (re) produce a macrosocial split of a complex, regional and ideological nature, which receives a technological dimension in the electoral discourse.
Keywords: electoral process; group nominations; social cleavages; discourse analysis; 316.342.7:[316.334.3:324(477)"2019"